Postpartum aortic dissection in a patient without Marfan’s syndrome - Yalçın, Mihriban (Turk J Obstet Gynecol, 2016)
Aortic dissection can occur in pregnancy or during the postpartum period without pre-existing disease and it is a rare but potentially life-threatening event. Herein, we present a young woman without Marfan’s syndrome who developed a postpartum ascending aortic dissection 5 days after cesarean section.